2000
DOI: 10.1103/physrevb.62.1580
|View full text |Cite
|
Sign up to set email alerts
|

Transport through a coupled quantum dot system: Role of interdot interactions

Abstract: The coupled double quantum dot system is modeled by a two impurity Anderson-type Hamiltonian and interdot Coulomb interaction is included. The conductance of this system is calculated using a nonequilibrium Green's-function formalism. We have evaluated conductance, peak splitting, and amplitude of conductance peaks as a function of Fermi energy for various values of parameters of the model Hamiltonian. It is demonstrated that an interdot interaction whose strength is assumed to be 10% of the ondot Coulomb inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 14 publications
1
26
1
Order By: Relevance
“…Later the same method was applied to some two-site models [206,207,208,209]. Multi-level systems were started to be considered only recently [210,211].…”
Section: General Nanoscale Quantum Transport Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Later the same method was applied to some two-site models [206,207,208,209]. Multi-level systems were started to be considered only recently [210,211].…”
Section: General Nanoscale Quantum Transport Theorymentioning
confidence: 99%
“…[205] Later the same method was applied to some two-site models. [206,207,208,214] Multi-level systems were started to be considered only recently. [210,211] For out-of-equilibrium situations (finite applied bias), there are some methodological unclarified issues for calculating correlation functions using EOM techniques.…”
Section: Coulomb Blockadementioning
confidence: 99%
“…Internal parameters of CQD are fully tunable thus allowing one to investigate, in a well-controlled manner, different regimes of interest. During the past years, the transport through series geometry of CQD has been studied extensively [10][11][12], using non-equilibrium Green function (NEGF) formalism, wherein it has been shown that current and differential conductance display oscillating variation with applied bias voltage. Inter-dot tunnelling splits the resonant peaks of conductance and transmission coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…These two starting points were often used in theoretical studies of transport properties across coupled QDs (see e.g. [17][18][19]). Though the unitary transformation which diagonalizes the DQD Hamiltonian can be performed in equilibrium and non-equilibrium cases, both approaches are not fully equivalent as electrons at different states are spatially apart.…”
Section: Introductionmentioning
confidence: 99%